Van der Waals engineering of ferroelectric heterostructures for long-retention memory - Wang, Xiaowei (2021)
The limited memory retention for a ferroelectric field-effect transistor has prevented the commercialization of its nonvolatile memory potential using the commercially available ferroelectrics. Here, we show a long-retention ferroelectric transistor memory cell featuring a metal-ferroelectric-metal-insulator-semiconductor architecture built from all van der Waals single crystals. Our device exhibits 17 mV dec−1 operation, a memory window larger than 3.8 V, and program/erase ratio greater than 107. Thanks to the trap-free interfaces and the minimized depolarization effects via van der Waals engineering, more than 104 cycles endurance, a 10-year memory retention and sub-5 μs program/erase speed are achieved. A single pulse as short as 100 ns is enough for polarization reversal, and a 4-bit/cell operation of a van der Waals ferroelectric transistor is demonstrated under a 100 ns pulse train. These device characteristics suggest that van der Waals engineering is a promising direction to improve ferroelectronic memory performance and reliability for future applications.